2018
DOI: 10.1097/mpg.0000000000001737
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms of Food Challenge‐proven Non‐IgE Cow's Milk Allergy Are Dissipated by Early School Age

Abstract: The non-IgE CM allergy with gastrointestinal symptoms diagnosed in infancy was a transient condition with good outcome. At an early school age, nearly all children have a good quality of life and a regular diet. The use of the double-blind, placebo-controlled food challenge was well-endorsed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…It may be that the observed difference between the three groups is thus more attributable to the original IgE sensitisation than CMA itself, but the number of patients in the subanalysis was too small to draw any firm conclusions. Previous studies support the idea that non–IgE‐mediated CMA is a benign condition that is not associated with an increased risk of atopic diseases 23 …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It may be that the observed difference between the three groups is thus more attributable to the original IgE sensitisation than CMA itself, but the number of patients in the subanalysis was too small to draw any firm conclusions. Previous studies support the idea that non–IgE‐mediated CMA is a benign condition that is not associated with an increased risk of atopic diseases 23 …”
Section: Discussionmentioning
confidence: 70%
“…Previous studies support the idea that non-IgEmediated CMA is a benign condition that is not associated with an increased risk of atopic diseases. 23 We observed that subjects with AE and CMA in infancy, compared with those with AE only, and unselected controls, had a higher lifetime prevalence of certain allergic symptoms: wheeze, noninfectious rhinitis and hay fever. For wheeze and noninfectious rhinitis, as well as rhinitis symptoms in the past 12 months, the associated aOR was significantly higher in the AE/CMA+ group compared with controls, but not in the AE/CMA− group compared with controls.…”
Section: Discussionmentioning
confidence: 73%
“…After the removal of duplicates and screening the abstracts of the remaining publications, 21 papers underwent full-text screening (Figure 1). Eleven of these were excluded (Table S1), [28][29][30][31][32][33][34][35][36] and 10 papers containing quantitative data on feeding difficulties were included in our systematic data analysis (Figure 1). 9,16,[37][38][39][40][41][42][43][44] We found no interventional studies in this systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
“…It was contended that too strict definitions may underestimate the incidence of CMA [7]. In any case, the condition presents an early resolution in the majority of cases, in particular the non-IgEmediated forms [5,6,8] 3. Non-IgE-mediated CMA and its gastrointestinal manifestations CMA is a spectrum of conditions ranging from the immediate.…”
Section: Epidemiology and Natural History Of Cmamentioning
confidence: 99%